Enhancing Work from Home (WFH) Motivation Among Employees in Private Sector - Y.C. Tay, Irene; Omar, Siti Sarah (Research in Management of Technology and Business, 2022)
The objective of this study was to explore the success factors on enhancing WFH motivation among employees in private sector. This study chooses employees in PCCS Group as subjects. A total of 210 effective questionnaires were collected through paper survey, and analysed by the SPSS Statistics. The collected data was analysed by using Descriptive Analysis, Regression Analysis and Correlation Analysis. The statistical results indicate the followings: 1. This study shows a significant correlation between WFH Motivation and Working Environment. 2. This study shows a significant correlation between WFH Motivation and Peer Support. 3. This study shows a significant correlation between WFH Motivation and Organization Support. The conclusions drawn from statistic findings were provided for the decision-makers and those researchers who would be interested in this field as references.